Disaggregating Okun's Law: A Case-Study for Macedonia - Danica Unevska Andonova; Magdalena Petrovska (Journal of Central Banking Theory and Practice, 2019)
Okun's law is one of the most widely-known stylized facts in the macroeconomic literature and policy. In this paper we study several aspects of Okun's law in Macedonia between 2004 and 2016. Aggregate indicators show a link between output and unemployment that is in line with other emerging markets and regional peers. We also find that the relationship has been somewhat weaker in recent years, which might be related to the recent job-intensive growth in the wake of structural reforms after the global financial crisis and particularly the subsequent European debt crisis. When investigating whether various expenditure components of GDP may cause different unemployment reactions, an important issue that has not been sufficiently addressed in the literature,we find that domestic demand has a stronger effect. We also provide several robustness checks to our main findings, and illustrate how they might be used to improve forecasting.
Keywords: E2; E24; C22; 330; Disaggregated Okun's law; unemployment; expenditure components of GDP